2020
DOI: 10.1101/2020.11.17.20233460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global seroprevalence of SARS-CoV-2 antibodies: a systematic review and meta-analysis

Abstract: BackgroundStudies reporting estimates of the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies have rapidly emerged. We aimed to synthesize seroprevalence data to better estimate the burden of SARS-CoV-2 infection, identify high-risk groups, and inform public health decision making.MethodsIn this systematic review and meta-analysis, we searched publication databases, preprint servers, and grey literature sources for seroepidemiological study reports, from January 1, 2020… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 47 publications
6
35
2
2
Order By: Relevance
“…Our findings showed that the frequency of positive IgG results was inversely associated with age. This finding is in line with the conclusion of a recent systematic review that confirmed a larger seroprevalence in people aged 18–64 years compared to the age group 65 years or above [ 4 ]. A Swiss study also showed that young children and older people (≥65 years) had significantly lower seroprevalence than the other age groups [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings showed that the frequency of positive IgG results was inversely associated with age. This finding is in line with the conclusion of a recent systematic review that confirmed a larger seroprevalence in people aged 18–64 years compared to the age group 65 years or above [ 4 ]. A Swiss study also showed that young children and older people (≥65 years) had significantly lower seroprevalence than the other age groups [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…The region-wise seroprevalence was 3.17% in Western Europe, 4.41% in Southern Europe, and 5.27% in Northern Europe. Another systematic review and meta-analysis posted in November 2020 reviews the results of 281 serosurveys [ 4 ]. The majority of surveys included in the meta-analysis reported IgG tests (83%) and the review showed a median seroprevalence of 3.2% in the general population worldwide, larger in healthcare workers and caregivers (6.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some overarching evaluations have systematically integrated data from multiple studies and countries. [1][2][3][4][5][6] These synthetic efforts probe what are typical estimates of spread and IFR, how heterogeneous they are, and what factors explain heterogeneity. An overview of these systematic evaluations comparing their methods, biases and inferences may help reconcile their findings on these important parameters of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The only systematic seroprevalence study in Iran took place in Gilan during April 2020 with an estimated prevalence of 21.0% (95%CI: 17.6% - 24.7%) across 528 household and community samples corresponding to an IFR of 0.09% (95%CI: 0.08% - 0.12%) [23]. More recent systematic reviews and meta-analysis of global seroprevalence of SARS-CoV-2 suggests that this seroprevalence study has moderate levels of bias and has overestimated the true prevalence by approximately a factor of 3.9 [24,25]. This implies that the corrected IFR of Gilan is more likely around 0.35% which is much closer to our 0.36% (95%CI: 0.34% - 0.39%) population-weighted IFR estimate.…”
Section: Discussionmentioning
confidence: 99%